Spike of interstitial PO2 produced by a twitch in rhythmically contracted muscle. Issue 1 (5th January 2021) - Golub, Aleksander S.; Nugent, William H.; Song, Bjorn K.
Abstract: Oxygen (O2 ) exchange between capillaries and muscle cells in exercising muscles is of great interest for physiology and kinesiology. However, methodical limitations prevent O2 measurements on the millisecond scale. To bypass the constraints of quasi‐continuous recording, progressive measurements of O2 partial pressure (PO2 ) in rhythmically contracting skeletal muscle were compiled to describe the O2 kinetics surrounding and including a single muscle contraction. Phosphorescence quenching microscopy measured PO2 in the interstitium of the rat spinotrapezius muscle. Measurements were triggered by contraction‐inducing electrical pulses. For the first 60 seconds, measurement preceeded stimulation. After 60, measurement followed with a progressive 20 ms increment. Thus, the first 60 measurements describe the overall PO2 response to electrical stimulation initiated after a 10 second rest period, while 61–100 (stroboscopic mode) were compiled into a single 800 ms profile of the PO2 transient surrounding muscle contraction. Thirty seconds of stimulated contractions decreased interstitial PO2 from a baseline of 71 ± 1.4 mmHg to an "active" steady‐state of 43 ± 1.5 mmHg. The stroboscopic mode compilation revealed an unexpected post‐contractile rise in PO2 as a 205 ms spike with a maximum amplitude of 58 ± 3.8 mmHg at 68 ms, which restored 58% of the PO2 drop from baseline. Interpretation of this phenomenon is based on classical experiments by G.V. Anrep (1935), who discovered the rapid thrust of blood flow associated with muscle contraction. In addition to the metabolic implications during exercise, the physiological impact of these PO2 spikes may grow with an increased rate of rhythmical contractions in muscle or heart. New&Noteworthy: The principal finding is a spike of interstitial PO2, produced by a twitch in a rhythmically contracting muscle. A possible mechanism is flushing capillaries with arterial blood by mechanical forces. A technical novelty is the PO2 measurement with a "stroboscopic mode" and progressively increasing delay between stimulator pulse and PO2 measuring. That permitted a 20 ms time resolution for a 205 ms spike duration, using an excitation flash rate one per second. Abstract : During muscle contraction when local oxygen tension is expected to decrease, we detected a spike (6), which is believed result from a bolus of arteriolar blood flushing the capillaries. This novel finding was made possible by combining phosphorescence quenching microscopy with a "stroboscopic mode" that allows for temporal scanning of oxygen gradients with a millisecond time resolution.